Applications of Camera Total Station System (CTSS) in the ConstructionSurveying - Khalaf, Abbas; Haidir, Muntaha; Jasim, Luma (Iraqi Journal of Science, 2024)
Engineering structures in general require at implementation conductingengineering surveys of the implementation stages of work to keep up with identicalimplementation of the technical specifications, on the other hand most of thefacilities task (large structures, towers, dams, bridges, etc…) require theconducting of periodic monitoring to determine any change could happen with timein the three-dimension( X,Y,Z).The traditional approach in this proposal for this business is by conducting a fieldsurvey using ground surveying devices in addition to the photogrammetry survey,regardless of the manner of the work requires the provision of a number of welldistributed ground control points for the purpose of the above required survey work.This research includes the application of(CTSS)system for a structural survey aboveas well as monitoring facilities disregarding the control points to provide cost,time and effort. The results using this technique(CTSS)are very promising (RMS inX= ±1.7 mm, Y= ±1.7 mm, Z= ±0.9 mm).which gives an overall precision of(RMS= ±2.6 mm).